Factors Related to Local Health Security Fund Management in Nakhon Pathom Province - สุมาลี, สุดารัตน์; คงศีล, สุคนธา; เจียมตน, สุขุม; รัตนรักษ์, ดารารัตน์; อินทรประสงค์ , ภูษิตา (Journal of Health Science of Thailand, 2024)
The local health security funds in Nakhon Pathom province had decreased expenditures in fiscal year 2021 compared to the previous years that it was expected to have problems in the operation. This research aimed to evaluate the management of the local health security fund in the province and to analyze the relationship between factors related to local government. This analytical cross-sectional study collected data in the fiscal year 2021 from personnel in the local health security fund committees who held a secretary or assistant secretary position at the committee. The population were 116 local health insurance funds; and the response was obtained from 110 funds or 94.83 percent. The research instrument had content validity of 0.94, and the Cronbach’s alpha coefficient was 0.86. Data were analyzed using the Chi-square and Fisher’s tests. The results showed that the management of local health security funds in Nakhon Pathom Province was at a high level. Budget factors of the funds were statistically significant and related to the management of the Health Security Fund i.e., the grant amount allocated by the National Health Security Office, contributions of local administrative organizations, and other income, (p<0.05). The management level was associated with the performance of financial assistant secretaries of the funds (p<0.05). Therefore, the National Health Security Office should allocate more funds to the local health insurance funds that had insufficient operational resources; and longitudinal study should be conducted to compare the performance among the funds and monitor the progress in order to indentify the operational problems.